Real-time digital trigger system for GTAF-II at CSNS Back-n white neutron source. (26th October 2021) - Xie, L.; Cao, P.; Yu, T.; Tang, X.; Jiang, Z.; An, Q.; Huang, X.; Li, C.; Li, J.; Gu, M.; Zhang, Q.; Luan, G.; et al.
Abstract: A 4-π detector array composed of 40 BaF_2 crystals named Gamma Total Absorption Facility II (GTAF-II) is designed for neutron capture cross-section (n, γ) measurements at Back-n white neutron source in China Spallation Neutron Source. The waveform digitizing (WFD) method is used to acquire the detector signals from GTAF-II accurately. To reduce the high data rate caused by the WFD method, a real-time digital trigger system is proposed in this paper. The trigger system is divided into local and global trigger processing to distinguish desired signals from various noises. The local trigger processing rejects photomultiplier noises and α particles by signal characteristics. The global trigger verification eliminates natural γ-rays according to the (n, γ) reaction mechanism. In order to realize the interaction between the local and global trigger processing, a high-precision global synchronization and trigger exchange network is constructed. Experiments with beams at back-n show that the trigger system provides a high data reduction factor. This trigger system covers the entire neutron energy range of 25 ms without dead time, and desired signals are acquired with full waveforms.